Orangutans geographic variation in behavioral ecology and conservation - Wich, Serge A. (Oxford : Oxford University Press, 2009)
Orangutan populations show extensive variation in behaviour and demography. This book carefully compares data from all orangutan research sites, examining the differences and similarities between orangutan species, subspecies and populations, and develops a theoretical framework in which these can be explained.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Orangutan -- Variation; Orangutan -- Ecology; Orangutan -- Behavior; Orangutan -- Conservation